Rates of intergranular environment assisted cracking in three-dimensional model microstructures - Jivkov, A; Marrow, T (2007)
Microstructure can have a significant effect on the materials' resistance to intergranular environment assisted cracking. Certain grain boundaries are susceptible to degradation by stress corrosion while others have high resistance, and it is recognised that increasing the fraction of resistant boundaries has a beneficial effect. A modelling investigation is reported in this work, which focuses on the effect of these boundaries on short crack growth rates in a microstructure corresponding to a sensitised austenitic stainless steel. The model uses a regular representation of the materials' microstructure and a simplified categorisation of grain boundaries as either resistant or susceptible to environment assisted cracking. While the resistant boundaries may fail only after a significant amount of plastic deformation, the rate of failure of the susceptible boundaries is a positive function of the local strain energy density. Results are presented to demonstrate the effect of increased fraction of resistant boundaries on crack propagation rates. Variation of the degree of sensitisation of the susceptible boundaries will have a similar effect. These support the expectation that grain boundary engineering may improve the material's resistance to environment-assisted cracking, with a significant effect on the incubation period for crack nucleus development. © 2007 Elsevier Ltd. All rights reserved.